Pengaruh Kemampuan TPACK dan Efikasi Diri Terhadap Kesiapan Menjadi Guru - Firmansyah, Fajar; Bahtiar, Moh. Danang (Jurnal Pendidikan Akuntansi (JPAK), 2025)
Teachers are one of the parties contributing to the achievement and determination of success in the education world. Moreover, the rapid changes in the world of technology and information have significantly impacted education. Therefore, it is necessary to have professional and sufficiently competent teachers. Teachers in the millennial era need to integrate technology and information into classroom learning to better support the quality of education in accordance with relevant competencies for the needs and developments of the times. This research aims to analyze the influence of TPACK ability on readiness to become a teacher, the influence of self-efficacy on readiness to become a teacher, and the simultaneous influence of TPACK and self-efficacy on readiness to become a teacher. This research uses a quantitative approach method. The number of respondents in this study is 84 students from the accounting education study program at Surabaya State University. The method applied for sampling is purposive random sampling technique. The data collection process was carried out by distributing questionnaires online, which were then processed using multiple linear analysis. The results of the study prove that TPACK significantly affects readiness to become a teacher, while self-efficacy does not significantly affect readiness to become a teacher. Simultaneously, the TPACK and self-efficacy variables affect readiness to become a teacher.